2013
DOI: 10.1186/1465-9921-14-52
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of clarithromycin in ventilator-induced lung injury

Abstract: BackgroundMechanical ventilation can promote lung injury by triggering a pro-inflammatory response. Macrolides may exert some immunomodulatory effects and have shown significant benefits over other antibiotics in ventilated patients. We hypothesized that macrolides could decrease ventilator-induced lung injury.MethodsAdult mice were treated with vehicle, clarithromycin or levofloxacin, and randomized to receive mechanical ventilation with low (12 cmH2O, PEEP 2 cmH2O) or high (20 cmH2O, ZEEP) inspiratory pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
(42 reference statements)
1
10
0
3
Order By: Relevance
“…The beneficial effects of fidaxomicin in CDI and the ability of other macrolides to possess anti-inflammatory responses in nongastrointestinal organs (14,15) led us to hypothesize that fidaxomicin may affect inflammatory responses against C. difficile toxin A by modulating signaling pathways that regulate the mucosal inflammation activated by this toxin. We were unable to test the ability of these drugs to inhibit the effects of toxin B in ileal loops in vivo, .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of fidaxomicin in CDI and the ability of other macrolides to possess anti-inflammatory responses in nongastrointestinal organs (14,15) led us to hypothesize that fidaxomicin may affect inflammatory responses against C. difficile toxin A by modulating signaling pathways that regulate the mucosal inflammation activated by this toxin. We were unable to test the ability of these drugs to inhibit the effects of toxin B in ileal loops in vivo, .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several 14-or 15-membered antibiotic macrolides, such as clarithromycin and azithromycin, which inhibit bacterial ribosome activity, possess anti-inflammatory effects (14,15). Other, nonantibiotic macrolides, including tacrolimus and sirolimus, are used predominantly as immunomodulators.…”
mentioning
confidence: 99%
“…These effects appear to be achieved via interference with mechanisms involved in the transcription of genes encoding these pro-inflammatory proteins [40-43]. …”
Section: Adjuvant Anti-inflammatory Strategies In Severe Pneumococcalmentioning
confidence: 99%
“…Sanz et al [ 30 ], reported in respect of an animal study in vivo that erythromycin exerts anti-inflammatory activity and inhibits leukocyte recruitment in the lung. In in vitro studies, results suggest that macrolides exhibit a suppressive effect on cytokines in models of acute inflammation [ 25 ], viral bronchiolitis [ 31 ] and ventilator-induced lung injury [ 32 ]. Anderson et al [ 33 ], have reported that the production of pneumolysin, a key virulence factor of the pneumococcus, is attenuated by exposure of this microbial pathogen to clarithromycin.…”
Section: Discussionmentioning
confidence: 99%